Voies périphériques comme centre de l’utopie. Le travail de la terre comme élément nodal de l’émancipation des femmes dans le Mexique rural - Céline Chenot (Les Cahiers ALHIM)
In Mexico as in Europe, the adjectives “religious” or “catholic” have rarely been used to describe feminism. This terminology appears problematic not only for some of the feminists who do not recognize religion as an emancipatory criterion, but also for the Catholic hierarchy, who in turn accuse them of misappropriation and misuse of religious principles (P. Aquino, 1998). Also, some theologians equate these two adjectives to a movement that cannot tackle the problems of female oppression (Tamez, 1998). Although these religious women - mainly Catholic - have remained in the shadows for a long time, they are nowadays actively involved in the emancipatory enterprise of women's empowerment and participate in the creation of new centers on the periphery. This article aims to analyze the land as a nodal element in the conceptions of ecofeminist struggles waged by two peripheral Catholic organizations.